2021
DOI: 10.1111/jonm.13357
|View full text |Cite
|
Sign up to set email alerts
|

Job crafting mediates the relation between creativity, personality, job autonomy and well‐being in Lebanese nurses

Abstract: Aim To better understand the functionality of job crafting and its relationship with personality and job autonomy in the context of non‐Western health care as an adaptive problem‐solving work behaviour that is related to creativity. Background Job crafting could be a strategy nurses use to solve problems as health care organisations become more unpredictable. Methods This cross‐sectional study sampled 547 nurses from seven hospitals in Lebanon. Data were analysed using structural equation modelling (SEM). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…The association between job autonomy and subjective well-being might differ across socio-cultural contexts. Ghazzawi et al found that the association between job autonomy and subjective well-being can only be achieved through engagement in increasing structural job resources and increasing challenging job demands, as collectivistic culture decreases employees’ perceptions of work autonomy ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between job autonomy and subjective well-being might differ across socio-cultural contexts. Ghazzawi et al found that the association between job autonomy and subjective well-being can only be achieved through engagement in increasing structural job resources and increasing challenging job demands, as collectivistic culture decreases employees’ perceptions of work autonomy ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed that autonomy was one of the strongest predictors of individuals’ life satisfaction and happiness. It exerted direct and indirect impacts on different SWB facets in Lebanese nurses, including life satisfaction, happiness, and positive and negative emotions ( 44 ). Bastida, Neira, and Lacalle-Calderon analyzed data from the European Social Survey and found that job discretion influenced SWB, which differed between males and females ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, high workload and time pressure lead to fatigue, which is not conducive to innovation (Ghazzawi et al, 2021). Nurses pointed out that limited resources are the main factor hindering innovation activities.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation takes a lot of time to think and work, so enough time is an important factor to promote innovation, and caregivers need time to think, explore different viewpoints and generate new ideas. However, high workload and time pressure lead to fatigue, which is not conducive to innovation (Ghazzawi et al, 2021). Nurses pointed out that limited resources are the main factor hindering innovation activities.…”
Section: Discussionmentioning
confidence: 99%
“…Openness and conscientiousness are the most influential personality traits (12). A cross-sectional study of nurses showed that creativity, job autonomy, and agreeableness were associated with the job crafting dimensions (17).…”
Section: Original Articlementioning
confidence: 99%